Taxonomer: an interactive metagenomics analysis portal for universal pathogen detection and host mRNA expression profiling. Issue 1 (December 2016) - Flygare, Steven; Simmon, Keith; Miller, Chase; Qiao, Yi; Kennedy, Brett; Di Sera, Tonya; Graf, Erin; Tardif, Keith; Kapusta, Aurélie; Rynearson, Shawn; Stockmann, Chris; Queen, Krista; et al.
Abstract Background High-throughput sequencing enables unbiased profiling of microbial communities, universal pathogen detection, and host response to infectious diseases. However, computation times and algorithmic inaccuracies have hindered adoption. Results We present Taxonomer, an ultrafast, web-tool for comprehensive metagenomics data analysis and interactive results visualization. Taxonomer is unique in providing integrated nucleotide and protein-based classification and simultaneous host messenger RNA (mRNA) transcript profiling. Using real-world case-studies, we show that Taxonomer detects previously unrecognized infections and reveals antiviral host mRNA expression profiles. To facilitate data-sharing across geographic distances in outbreak settings, Taxonomer is publicly available through a web-based user interface. Conclusions Taxonomer enables rapid, accurate, and interactive analyses of metagenomics data on personal computers and mobile devices.